IMPROVING STUDENTS' VOCABULARY MASTERY THROUGH TEAM GAMES TOURNAMENT TECHNIQUE IN RECOUNT TEXT - Alfanny Putri Hidayat; Trisnendri Syahrizal (IKIP Siliwangi, 2020)
This research focuses on the effect of recount text to improve vocabulary mastery through Team Game Tournament (TGT) .The methotology which is used by using action research.The subjects are the grade I students of SMA PASUNDAN 3 Cimahi.Two classes, science class and social class were taken the subject of observation. This research object is to find the effect and extent of recount genre to improve students’ ability in vocabulary mastery where the population and sample is taken from grade I students of SMA PASUNDAN 3 Cimahi.After the data been collected, the researcher finds out that the students in the grade I has improve in their vocabulary. It has been also caused by quiz through Team Game Tournamentc(TGT) practice of recount text, that recount text can be applied to improve the vocabulary mastery skill of the students.